The effectiveness of a 0.25% lemongrass (Cymbopogon citratus) essential oil mouth spray and a 0.12% chlorhexidine mouthwash against supragingival plaque in wearers of fixed orthodontic appliances: Efektivitas mouth spray minyak atsiri daun serai (Cymbopogon citratus) 0,25% dan mouthwash klorheksidin 0,12% terhadap plak supragingiva pada pemakai peranti ortodonti cekat - Korniala; Dina Tri Ramadhani; Ricky Amran; Azmil Hadi (Makassar Dental Journal PDGI Makassar, 2026)
The use of fixed orthodontic appliances increases the risk of plaque accumulation due to the numerous retentive areas around the brackets and wires. 0.12% chlorhexidine mouthwash is the gold standard for plaque control, but its long-term use can cause side effects. Lemongrass essential oil (Cymbopogon citra-tus) possesses antibacterial activity, making it a potential safer alternative mouthwash. Differences in the effectiveness of 0.25% lemongrass essential oil mouth spray and 0.12% chlorhexidine mouthwash in reducing supragingival plaque scores were reported among students using fixed orthodontic appliances. A quasi-experimental study with a pre-test and post-test control group design was conducted on 30 participants (15 in each group). Plaque scores were mea-sured using the OHI-S before and after the intervention. Analysis was performed using a paired t-test and an independent samples t-test (?=0.05). The 0.25% lemongrass mouth spray reduced plaque scores from 56.64% to 25.44% (p=0.001). The 0.12% chlorhexidine mouthwash reduced the plaque score from 58.37% to 25.87% (p=0.001). A comparison between the groups showed p=0.762, indicating no significant difference between the two. It is concluded that both agents are equally effective in reducing plaque scores, and 0.25% lemongrass mouth spray may be a safer alternative to 0.12% chlorhexidine.